The Effect of Vitamin K2 on Osteogenic Differentiation of Dental Pulp Stem Cells: An In Vitro Study - Rasouli-Ghahroudi, Amir Alireza; Akbari, Solmaz; Najafi-Alishah, Mohammad; Bohloli, Mahbobeh (Regeneration, Reconstruction & Restoration (Triple R), 2017)
Introduction: dental pulp stem cells (DPSCs) have been shown to have great capacity to differentiation toward the osteoblast lineage and they can be considered as a great cell source for bone tissue engineering. The vitamin K family, especially vitamin K2 (MK-4), have been shown to have an osteoprotective role. In this study, we have investigated the effect of various concentrations of MK-4 on differentiation of DPSCs into osteoblast. Materials and Methods: DPSCs were isolated and characterized to expression the mesenchymal markers. These cells were treated with osteogenic medium with and without of various concentrations of MK-4 for 14 days. Osteogenic capability and extracellular calcium deposition were assessed by ALP assay and alizarin red staining, respectively, at zero, 7, 14 days after induction. Result: the additional of MK-4 at concentration of 10 µM with osteogenic medium had a significant effect on differentiation DPSCs into osteoblast (P<0.05) at 14 day, as it confirmed by both ALP activity assay and alizarin red staining. Conclusion: MK-4 can promote differentiation of DPSCs into osteoblast in vitro so have a potential to be considered in improvement of cell-based bone tissue engineering therapies.